SEXUAL EDUCATION IN SCHOOL AND ITS OBSTACLES TO AN ESSENTIAL REALITY - Barbosa de Sousa Júnior, José (Revista Gênero e Interdisciplinaridade, 2024)
The article addresses the importance of sexual education in schools and the challenges that hinder its effective implementation. Emphasis is placed on addressing issues related to sexuality in the educational environment, aiming to provide appropriate information to students, promoting a healthy and conscious understanding of the subject with the goal of understanding the relevance of the pedagogical approach in sexual education experienced in the classroom by teachers and students at school. Through the qualitative method, the research is based on the exploration of articles, among other documents available in databases and virtual libraries. Additionally, obstacles that impede the realization of this reality are discussed, such as cultural taboos, resistance from certain sectors of society, as well as the absence of comprehensive educational policies. The article highlights the need to overcome such barriers to ensure inclusive sexual education that contributes to the holistic development of students and promotes healthy and respectful relationships throughout their lives in this essential cycle.